Dual‐spray hydrogen/deuterium exchange (HDX) reactions: A new method of probing protein structure. (8th June 2016) - Rashid, Shaan; Overton, Sean; Mazigh, Bihac; Mayer, Paul M.
Abstract : Rationale: Traditionally, hydrogen/deuterium exchange (HDX) reactions are done in the solution phase. This usually involves incubating the protein with a suitable deuterating agent then acidifying the solution to quench the reaction. A more efficient method may be to conduct the reaction within the ion source of a mass spectrometer and subsequently analyze the products. Methods: Using the two electrospray emitters equipped on the Waters Synapt G1 mass spectrometer, HDX reactions were conducted within the ion source region in a controlled fashion ('dual‐spray'). Peptide and protein solutions were electrosprayed through one emitter and the deuterating agent D2 O through the secondary electrospray emitter. For the relatively small peptides, Phe‐Leu‐Glu‐Glu‐Leu and oxytocin, the yield of products was calculated using deconvolution functions. Electrospray ionization (ESI) charge‐state distributions and average number of deuterium exchanges were used to probe secondary and tertiary structures of ubiquitin, lysozyme, and cytochrome c in their native and unfolded states. Results: Clear shifts in isotope distributions indicated HDX occurring within the ion source. By ion mobility, simultaneous deuterium exchange for two isobaric species, the oxytocin monomer and dimer, was observed. For denatured ubiquitin, the 12+ and 13+ charge states have a lower average number of exchanges relative to the lower charge states which indicates that these charge states have segments which restrict the access of D2 O. Lysozyme has a linear relationship between the charge state and the average number of exchanges, indicating that lysozyme becomes increasingly unfolded as the charge state increases. The dual‐spray HDX method was paired to high‐performance liquid chromatography (HPLC) to demonstrate the applicability of the technique for probing gas‐phase structures in protein mixtures. Conclusions: ESI droplets formed from a secondary emitter penetrate primary ESI droplets and change the solvent composition. Dual‐spray HDX is demonstrated to be a more efficient method for probing the structure of proteins than solution‐phase HDX since the acid quenching step can be surpassed. Copyright © 2016 John Wiley & Sons, Ltd.